Analyzing the Role of the Concept of Urban Socialization in the Urban Public Space Based on the Status of Human Dignity - Maryam Sabokkhiz; Esmail Shieh (تحقیقات کاربردی علوم جغرافیایی)
Human dignity is a concept that can have a significant impact on urban public space. In this sense, it speaks of the value of human beings and their status as a thoughtful and spiritual being. Discovering this valuable feeling in an environment that is widely used by citizens is important to the research. The subjective and interactive nature of this phenomenon The purpose of this study was to analyze explicit inductive qualitative content analysis as a research method and to interpret contextual data obtained from in-depth unstructured interviews and field observations, and its perception among various actors and how human dignity was generated. Used. The data were analyzed through a systematic coding process with the aim of classifying concepts up to three levels of abstraction. The selection of participants in this study was purposeful and aimed at developing concepts to reach saturation. The findings of this study indicate that the concept of socialization is one of the most important factors in people's perception of human dignity. It is conceptualized with other concepts such as loss of personal distance, development of social communication, intimacy, social diversity and unity with the environment and society. Is formed. What is of interest is the relationship between these factors and the complexity of their relationships that have led to the formation of a sense of human dignity in individuals. Although the multifaceted concept of human dignity will be able to accommodate the broad concepts and meanings that are involved in this study The concept of socialization of urban public space has been carefully considered.